2012
DOI: 10.1021/op200386u
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Spherical Particles of 1,1-Diamino-2,2-dinitroethene (FOX-7) Using a Micellar Nanoreactor

Abstract: The need and preparation of spherical 1,1-diamino-2,2-dinitroethene (FOX-7) particles to meet certain special applications in high explosives and propellant formulation have been illustrated. Preparation of spherical FOX-7 particles by using a microemulsion technique has not been reported in the literature. In the present study, the preparation of spherical FOX-7 particles has been described using the novel concept of a micelle-based nanoreactor. Micelle-based nanoreactors have been prepared using a microemuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 5 publications
2
32
0
Order By: Relevance
“…5,6 Such facts indicated that the activity free energy of the nitration should be considerably low, and the HSO 4 À -induced path A may be more favorable way than the direct path, which is in very good agreement with the experimental results. 6 Additionally, in view of the fact that a higher H 2 SO 4 concentration may benet an easier formation of NO 2 + along with a more difficult dissociation of H 2 SO 4 to form HSO 4 À , the concentration of H 2 SO 4 should be well controlled.…”
Section: Resultssupporting
confidence: 82%
“…5,6 Such facts indicated that the activity free energy of the nitration should be considerably low, and the HSO 4 À -induced path A may be more favorable way than the direct path, which is in very good agreement with the experimental results. 6 Additionally, in view of the fact that a higher H 2 SO 4 concentration may benet an easier formation of NO 2 + along with a more difficult dissociation of H 2 SO 4 to form HSO 4 À , the concentration of H 2 SO 4 should be well controlled.…”
Section: Resultssupporting
confidence: 82%
“…Since it was reported in 1998 [2], it has quickly been the subject of explosives research in various countries of the world. Many researchers have focused on the theoretical calculation, synthesis, thermal properties, and nanostructure of FOX-7 [3][4][5][6][7][8][9][10]. Previous results on the physical and chemical characterization of FOX-7 have demonstrated that it possesses good thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that nanocrystals of energetic materials can not only decrease the mechanical sensitivity, but also help for improving the combustion and detonation properties as compared to coarse energetic materials [5][6][7][8]. Various techniques, such as electrospray crystallization, ultrasound-and spray-assisted crystallization, direct write ink-jet, microemulsion, rapid expansion of supercritical solutions, solvent-antisolvent crystallization, and sol-gel method, had been employed to fabricate nanocrystals of high explosives, including cyclotrimethylene trinitramine (RDX) [9], cyclotetramethylene tetranitramine (HMX) [10,11], hexanitrohexaazaisowurtzitane (CL-20) [12], 1,1-diamino-2,2-dinitroethylene (FOX-7) [13], 5-nitro-2,4-dihydro-3H-1,2,4-triazole-3-one (NTO) [14], 2,2',4,4'-,6,6'-hexanitrostilbene (HNS) [15], 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) [16,17], etc.…”
Section: Introductionmentioning
confidence: 99%